Relações entre línguas e a experiência do aprender surdo - Soler, Priscila Silveira (Universidade Federal de São Carlos, 2022)
This research analytically approaches the relational process between the Brazilian Sign Language (Libras) and the Portuguese Language (PL) in the appropriation of writing by deaf signers. A certain hybridization is assumed in the learning of PL that results from the singular experience materialized in the deaf body from its interactions with Libras, adopted here as a matrix language. Although research in the area of deafness discusses the importance of differentiated teaching of PL for the deaf, based on proposals for teaching a second language (L2), methodological problems are still present in this area. Research points as a strategy to repair this, the applicability of teaching materials and new teaching methods. However, as the limitations in teaching the deaf are still evident, the objective of this study was to analyze, from the deaf perspective, the process of learning written PL based on visual experience, pointing out if there is effectively a relational knowledge between languages (oral, written and signed) that adds to this process a new place (inscribed) in deaf bodies. Thus, the deaf perspective is taken as a focus for the process of learning written PL, based on visual experience, pointing out if there is effectively a relational knowledge between languages (written and signed oral) that adds a new place of inscription of these (hybrid) practices in deaf bodies. The perspective adopted did not seek to produce teaching materials with second language methodologies based on oral languages, but pointed to the necessary attention to teaching practices and teaching resources based on listening to deaf subjects and their singularities. For this, it was necessary to describe the concepts of mother language and additional language, built based on the concept of experience matrix in Michel Foucault, therefore, in the philosophies of difference, and with a theoretical-methodological path with Genealogical inspiration. The hypothesis was that the deaf visual experience constitutes a unique place and from this matrix their experiences with the writing of the Portuguese language are forged. It is a theoretical research with empirical data analyzed from the theoretical-philosophical perspective of difference. The research instruments were: observation, recording in a field notebook, interview with deaf participants and conversation circles with the intervention of the researcher. As a result of the research, it is possible to affirm that the process of learning PL is forged in the experience with sign language and through it, new ways of life are produced, constituted in the Matrix of experience in which the subject is traversed. In this way, the experiences lived through Libras and PL assert themselves as constituting the subject's formative field and constructive practices that shape him as he does. It is, therefore, in the interconnection between Libras and PL - in the relationship between them and in the midst of these languages - that this deaf ethos is constituted. In short, the research can significantly contribute to the advancement of this theoretical reflection and adds a new look to the teaching of PL for the deaf, in the conceptual expansion for the area in an approach that privileges the deaf ontology and the bodily experiences that result from it.
Relations between languages ​​and the experience of learning deaf
Keywords: Educação especial; Educação de surdos; Língua portuguesa para surdos; Língua adicional; Matriz de experiência; Special education; Deaf education; Portuguese language for the deaf; Additional language; Experience matrix; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM